2020
DOI: 10.15586/qas.v12i3.755
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and dissipation behavior of pesticide residues in parsley (Petroselinum crispum) under field conditions

Abstract: The residue level, dissipation behavior, and dietary intake risk of chlorpyrifos-methyl, dimethoate, permethrin, iprodione, metalaxyl, and propargite in parsley (Petroselinum crispum) were investigated under field conditions. Extraction and determination of pesticide residues were carried out by a quick, easy, cheap, effective, rugged, and safe (QuEChERS) method and a gas chromatography/tandem mass spectrometry (GC/MS/MS) system, respec-tively. Dissipation of chlorpyrifos-methyl, dimethoate, permethrin, iprodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 51 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…When metalaxyl‐M was applied with MAN + BOS + KRE (Mix 8), there was a statistically significant difference between the concentration of metalaxyl‐M on day 14 (PHI) and that of metalaxyl‐M applied alone (Table 3). Previous studies on the dissipation of metalaxyl‐M found that the half‐life of metalaxyl‐M was 5.3 and 6.0 days for sites 1 and 2, respectively, in Swiss chard in Korea, 35 and 2.4 days in parsley in Iran 36 …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…When metalaxyl‐M was applied with MAN + BOS + KRE (Mix 8), there was a statistically significant difference between the concentration of metalaxyl‐M on day 14 (PHI) and that of metalaxyl‐M applied alone (Table 3). Previous studies on the dissipation of metalaxyl‐M found that the half‐life of metalaxyl‐M was 5.3 and 6.0 days for sites 1 and 2, respectively, in Swiss chard in Korea, 35 and 2.4 days in parsley in Iran 36 …”
Section: Resultsmentioning
confidence: 94%
“…Previous studies on the dissipation of metalaxyl-M found that the half-life of metalaxyl-M was 5.3 and 6.0 days for sites 1 and 2, respectively, in Swiss chard in Korea, 35 and 2.4 days in parsley in Iran. 36…”
Section: Metalaxyl-mmentioning
confidence: 99%
“…On the other hand, nature of the end products of natural degradation is distrustful because toxicity of the pesticide may be increased or decreased upon conversion to another compound (Menzie, 1972;Gavrilescu, 2005). As well, the persistence of pesticide residuals is also unrevealed because pesticide residuals are found in different matrices in the environment in different forms (Darko et al, 2008;Nag and Raikwar, 2011;Silva et al, 2019;Heshmati et al, 2020). The intensive and indiscriminate usage of pesticides has resulted in serious health issues both in human and other life forms, as well as there exist adverse side effects to the environment (Jeyaratnam, 1985;Kumar et al, 2013b;Sharma and Singhvi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since these products are consumed daily as food, the occurrence of pesticide residues can pose potential risks to the consumers' health and increase the chance of various chronic diseases and cancers (Mrema et al 2013;Hassani et al 2015;Guo et al 2016;Georgiadis et al 2018;Heshmati et al 2021). Thus, monitoring pesticide residues in agricultural products and food and performing risk assessments based on the residue data by evaluating parameters such as estimated daily intake (EDI) and hazard quotient (HQ) are crucial and have received considerable attention recently (Moretto et al 2015;Tsatsakis et al 2017;Dong et al 2017;Dong et al 2018;Bopp et al 2018;Pico et al 2018;Heshmati et al 2020aHeshmati et al , 2020b.…”
Section: Introductionmentioning
confidence: 99%